Determinants of Small Medium Micro Business Empowerment: Systemic Literature Review - Aidil Amin Effendy; Muhamad Apep Mustofa; Raden Ruli Basuni; N Nurjaya; Denok Sunarsi (Universitas Dharma Wacana, 2022)
The purpose of this study is to determine the determinants of MSME Empowerment and what factors determine MSME Empowerment in the Globalization Era. This study uses a descriptive exploratory approach by using an approach to literature review or literature study, which refers to various literatures, such as books, dissertations, scientific journals and the internet. All the descriptions of existing ideas are combined in a single framework of thought. The results of the study can be concluded, From the discussion that has been described, it can be concluded that the determinants of MSME Empowerment are the role of the government in empowering MSMEs in Indonesia which is the driving force for the success of MSMEs in an effort to rise during the pandemic, with one of the main policies being to encourage lending to MSMEs. , such as People's Business Loans, Independent Business Loans, Productive Business Loans and other credit financing. The role of banking in financing Micro, Small and Medium Enterprises (MSMEs) has a very important contribution because MSMEs will be able to develop if they have sufficient capital to run their business. In addition, the factor that determines the empowerment of MSMEs is that the government needs to establish policies for MSMEs that receive credit financing according to a priority scale, then provide guidance and assistance as long as MSMEs use their business loans, facilitate relationships between MSMEs and other parties and provide access to marketing information and ease of marketing. for MSMEs to offer their products or services to be easily sold in the market.